Media Promosi Kesehatan Berbasis Web Sehat Dengan Toga (SEDEGA) Dalam Meningkatkan Pengetahuan Masyarakat Kelurahan Labuh Baru Timur Provinsi Riau - Safitri, Yunni; Safitri, Feby Eka; Putra, Muhammad Hafiz; Mukti, Candra; Febriantoro, Rendi (Jurnal Cendekia Mengabdi Berinovasi dan Berkarya, 2025)
Herbal plants have long been known as natural ingredients that are beneficial for health, but among housewives, their use is often limited to cooking spices. Many people are not aware that herbal plants such as turmeric, ginger, betel leaves and ginger can be processed into natural and efficacious herbal medicines. Lack of knowledge about the benefits and methods of processing herbal plants is one of the main obstacles. This website exists to provide education to housewives about the potential of herbal plants as natural medicines. Information includes an introduction to herbal plants, their health benefits, as well as practical steps in processing them into safe and effective potions. With this education, housewives are expected to be able to make maximum use of herbal plants, not only for the kitchen, but also as an economical and natural family health solution. Apart from that, this initiative also aims to preserve traditional knowledge and support community health in a sustainable manner.